Mitigation of coupled wind-wave-earthquake responses of a 10 MW fixed-bottom offshore wind turbine - Yang, Yang; Bashir, Musa; Li, Chun; Michailides, Constantine; Wang, Jin (My University, 2020)
In this paper we present a study on the mitigation of dynamic responses of a 10 MW monopile offshore wind turbine under coupled wind-wave-earthquake excitations. We have developed and validated the generic seismic coupled analysis and structural control architecture tool to overcome the limitation of numerical tools when examining the wind-wave-earthquake coupling effects. We investigated the dynamic responses of a 10 MW monopile offshore wind turbine under different loading combinations and found that the earthquake loading increases the tower-top displacement and pile-cap moment by 47.6% and 95.1%, respectively, compared to the wind-wave-only condition. It is found that the earthquake-induced vibration in the fore-aft direction is mitigated by the wind and wave loadings due to the energy dissipated by the aerodynamic and hydrodynamic damping. In addition, the tower responses are dominated by the earthquake excitation. In order to alleviate the tower vibration induced by the earthquake, we implemented the structural control capability within the tool using tuned mass dampers. The tuned mass dampers with appropriately selected design parameters achieve a larger mitigation on the tower-top displacement for the earthquake-only condition compared to the coupled-loading scenario. The reason is that the tuned mass damper is only effective in mitigating tower vibration, and it is not capable of reducing the tower elastic deformation which is the major contribution of the tower displacement for the coupled-loading condition. In addition, we have found that a heavier tuned mass damper requires a lower tuned frequency to achieve a larger mitigation. A configuration for the mitigation control of the 10 MW offshore wind turbine is suggested by using a 5% mass ratio of the tuned mass damper.
Keywords: Offshore wind turbines; Tuned mass dampers; Wind-wave-earthquake analysis; Structural control; Earthquake excitation